Phenotypic characterization of Pomeranians with or without Chiari-like malformation and syringomyelia - Santifort, Koen M.; Carrera, Ines; Bossens, Kenny; Mandigers, Paul J. J. (Frontiers in Veterinary Science, 2023)
Chiari-like malformation (CM) and syringomyelia (SM) are frequently diagnosed conditions in small and toy dog breeds, such as the Cavalier King Charles Spaniel and Griffon-Bruxellois. CM/SM is only rarely reported in Pomeranians in literature to date. The aims of this study are to 1/ describe the phenotype of Pomeranians with or without CM/SM and 2/ evaluate for differences and associations between CM/SM and owner-reported clinical signs (ORCS) or signalment factors. From February 2015 to June 2023, historical data and signalment (including country of origin, pedigree, sex and neuter status, age, and body weight) and ORCS of Pomeranians were recorded at multiple institutions. MRI studies of all dogs were evaluated for classification of CM/SM. Additionally, quantitative measurements were performed for SM. A total of 796 dogs from 22 different countries were included. Total prevalence of CM was 54.9% (437/796) and the prevalence of SM was 23.9% (190/796). The top 5 ORCS included 1/ scratching with skin contact, rubbing head or ears, or both (57.6% of dogs with ORCS), 2/ air licking (30.7% of dogs with ORCS), 3/ spontaneous signs of pain (26.0% of dogs with ORCS), 4/ persistent licking front and/or hind paws (22.6% of dogs with ORCS), 5/ phantom scratching (22.6% of dogs with ORCS). Phantom scratching, vocalization, head shaking, spontaneous signs of pain, and air licking were associated with having SM. There were no statistically significant associations between quantitative syrinx measurements and ORCS. There were statistically significant associations between CM classification and 1/ country of origin, 2/ having a pedigree, and 3/ age. There were statistically significant associations between SM classification and 1/age and 2/ body weight. This is the first large study evaluating CM/SM in the Pomeranian dog breed. Veterinary clinicians can use these findings to increase the likelihood of correctly determining the presence or absence of CM/SM in Pomeranians. Breeders may consider using the information regarding signalment factors as well as ORCS associated with CM/SM classifications to select dogs for screening procedures. An MRI-based diagnosis is needed to properly ascertain the exact CM/SM status of their breeding stock until a fool-proof characteristic or genetic marker is found.